2018
DOI: 10.5539/jas.v10n2p352
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Substrates for Jenipapo (Genipa americana L.) Seedlings Production

Abstract: Jenipapo (Genipa americana L. Rubiaceae) is a native species not endemic to Brazil and found in several biomes. The objective of this work was to evaluate the emergence and growth of seedlings cultivated in different substrates. Treatments were made of: T1 (fertilized soil), T2 (fertilized soil + coconut fiber), T3 (fertilized soil + sand), T4 (sand + coconut fiber), T5 (bovine manure + coconut fiber), and T6 (bovine manure + sand). The experiment consisted of a completely randomized design, with six treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…However, the results of the present study were higher than those obtained by Costa et al (2007) for genipap seedlings with total biomass of 3.82 g using a substrate containing black soil + carbonized rice husk + bovine manure in the ratio 1:1:1. Silva et al (2018) reported that substrates fertilized soil, fertilized soil + coconut fiber, fertilized soil + sand and bovine manure + sand were more efficient for genipap seedlings.…”
Section: Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of the present study were higher than those obtained by Costa et al (2007) for genipap seedlings with total biomass of 3.82 g using a substrate containing black soil + carbonized rice husk + bovine manure in the ratio 1:1:1. Silva et al (2018) reported that substrates fertilized soil, fertilized soil + coconut fiber, fertilized soil + sand and bovine manure + sand were more efficient for genipap seedlings.…”
Section: Speedmentioning
confidence: 99%
“…The chemical fertilization under 40% shade cover using substrates rich in organic compounds favored the formation of high-quality seedlings, showing higher values of root collar diameter, plant height and shoot and root biomass accumulation (MORAES NETO;GONÇALVES, 2000). According Silva et al (2018) the substrates fertilized soil, fertilized soil + coconut fiber, fertilized soil + sand and bovine manure + sand promoted better genipap seedlings production. Sassaqui, Terena and Costa (2013) reported that substrates composed of "50% bovine manure + 50% cassava stem" and "50% bovine manure + 50% Vida Verde®" used in agricultural greenhouses, and those of "50% bovine manure + 50% vermiculite" and "25% bovine manure + 25% cassava stems + 25% Vida Verde® + 25% vermiculite" under black shade cover, formed high-quality genipap seedlings, although a more in-depth study on different combinations of greenhouses and substrates will help in the seedling cultivation of changing genipap more efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…In Colombia, this species is distributed in the departments of Antioquia, Quindío, Risaralda, Amazonas, Cundinamarca, and Boyacá, where it is called jagua or huito (Pinto-Ruiz et al, 2018). Said species is used both for its wood characteristics and its fruit -which has various medicinal, nutritional, and cosmetic attributes-thus leading to an extractive activity without any care for conservation or knowledge about the species (Santos et al, 2011;Silva et al, 2018). Jagua trees are fastgrowing and a good option of economic importance for small farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the evaluation of biotypes of the same species collected in contrasting environments would be expected to obtain a differential response of genotypes under particular environmental evaluation conditions. In the case of G. americana, studies evaluating the physiological efficiency both indirectly (Barbosa et al, 2007;Mielke et al, 2003) and directly (Petit & Montagnini, 2004;Santiago & Paoli, 2007;Santiago et al, 2018;Silva et al, 2018) have been reported. However, this type of work is still scarce for this species.…”
Section: Introductionmentioning
confidence: 99%
“…The substrate is one of the inputs that have stood out in importance, due to its wide use in the production of seedlings (Kratz, Wendling, Nogueira, & Souza, 2013). It is an essential input that directly influences the seed germination, due to its structure, aeration, water holding capacity, pathogens, among others, which may favor or hinder seed germination (Silva et al, 2018;Guedes, Alves Gonçalves, França, Moura, & Santos, 2011;Moraes, Garcia, Souza, & Moreira, 2007). To produce seedlings of forest species, some factors should be considered, including the selection of the correct substrate and its fertilization, since interactions with acclimation factors during the production are important to ensure a quality end-product.…”
Section: Introductionmentioning
confidence: 99%